2015
DOI: 10.1021/la505035k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Macroscale Wetting Equations on a Microrough Surface

Abstract: The wettability of critical droplets on microscale geometric rough surfaces has been investigated using a density functional theory approach. In order to analyze the effect of roughness on nucleation free-energy barriers, the local density fluctuations at liquid-solid interfaces induced by the multi-interactions of a corner substrate are presented to interpret the interfacial free-energy variations, and the vapor-liquid-solid contact line tensions are derived from the contact angles of nuclei to account for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Another important quantity to consider when dealing with nanoscale systems is the line tension . First defined by Gibbs, for a three phase system, the contact line tension is the excess free energy per unit length along the gas–solid interface .…”
Section: The Difference Of Nanomentioning
confidence: 99%
See 1 more Smart Citation
“…Another important quantity to consider when dealing with nanoscale systems is the line tension . First defined by Gibbs, for a three phase system, the contact line tension is the excess free energy per unit length along the gas–solid interface .…”
Section: The Difference Of Nanomentioning
confidence: 99%
“…In these calculation, interatomic and intermolecular forces governed by Lennard‐Jones potential and the Hamaker theory are taken into account . Discrepancies between the contact angles predicted by macroscopic models and the actual contact angle measured on nanorough substrates was often attributed to significant line tension contribution . Recently Dietrich and co‐workers combined classical density functional theory to the string method and demonstrated that metastable states and deviation from the original theories arose from contact line pinning on nanodefects .…”
Section: Element Of Responsementioning
confidence: 99%
“…The resulting energy barriers and critical radii were presented. In a subsequent work, line tensions, contact angles, and Tolman lengths were studied, and the effect of surface roughness on the wettability was investigated …”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent work, line tensions, contact angles, and Tolman lengths were studied, 44 and the effect of surface roughness on the wettability was investigated. 45 The effect of surface roughness was also examined by Malijevsky, 46 who evaluated the prediction of Wenzel's law: that an increase of surface roughness leads to an increase in wettability of the fluid. The number of particles was constrained to a fixed value using a Lagrange multiplier, and the Helmholtz energy functional consists of an FMT 47,48 and a mean-field approach for the repulsive and attractive contributions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the theoretical part, we attempted to interpret the hydrophobic mechanism of different rubber surfaces. Within the framework of our previously proposed three-dimensional density functional theory (3D-DFT), 24 the asymmetric interactions between particle and water molecules were described by the Hamaker theory, and the net and rough surfaces of SBR, polymethyl-vinylsiloxane (PMVS), and natural rubber (NR) were systematically investigated to decipher the effects of chemical and geometric characteristics on hydrophobicity and superhydrophobicity. According to surface morphologies and the interactions of rubber-water and particle−water, different droplet nucleation behaviors were considered to evaluate the contribution of the corner effect and line tension.…”
Section: Introductionmentioning
confidence: 99%